2012
DOI: 10.3354/meps09564
|View full text |Cite
|
Sign up to set email alerts
|

Partition of planktonic respiratory carbon requirements during a phytoplankton spring bloom

Abstract: We studied the effect of variable phytoplankton biomass and dominance of the diatom Skeletonema marinoi on the planktonic community respiratory carbon requirement over a period of 14 d (14 to 28 April 2008) in 3 different mesocosms filled with natural water at Espegrend marine biological field station in Raunefjord, Norway. The carbon requirement was measured on mesozooplankton (the calanoid copepod Calanus finmarchicus) and 3 other size fractions of plankton -< 200 µm (dominated by microzooplankton), <15 µm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(108 reference statements)
1
2
0
Order By: Relevance
“…In both sites a clear link between nutrient dynamics and metabolic activity was observed. The changes in nutrients and standing biomasses coincided with increased CR during the spring bloom, supporting established findings on the positive relationship between blooms and CR (e.g., Iriarte et al., 1991; Md Amin et al., 2012). The negative significant relationship between DIN and CR can be further explained by the fact that DIN is readily utilized by phytoplankton during production, leading to increased CR as labile organic matter becomes available both for heterotrophs and autothrophs (Mantikci et al., 2017, 2020; Sadro et al., 2011, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In both sites a clear link between nutrient dynamics and metabolic activity was observed. The changes in nutrients and standing biomasses coincided with increased CR during the spring bloom, supporting established findings on the positive relationship between blooms and CR (e.g., Iriarte et al., 1991; Md Amin et al., 2012). The negative significant relationship between DIN and CR can be further explained by the fact that DIN is readily utilized by phytoplankton during production, leading to increased CR as labile organic matter becomes available both for heterotrophs and autothrophs (Mantikci et al., 2017, 2020; Sadro et al., 2011, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, these altered interactions could lead to distinct microbial loop patterns in the carbon cycle, ultimately impacting CR. A study using mesocosm experiments in a Norwegian fjord showed that during the spring bloom, microzooplankton and nanoplankton have carbon requirements equivalent to more than half of primary production, while bacterioplankton are intermediate and variable (Md Amin et al., 2012). Perhaps because of this, the role of other heterotrophs in CR outweighs that of the bacterial compartment, which may explain why we were unable to detect significant seasonal differences.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration measurements were taken with a dynamic luminescence quenching-based system (Sensor Dish Reader, SDR2; PreSens GmbH, Germany) to allow continuous measuring. This system has been used previously in a similar way (Warkentin et al, 2007(Warkentin et al, , 2011Amin et al, 2012). Two plates containing 24 samples of 5 mL each were incubated at each temperature, and respiration measurements were performed for 12 h to obtain a sufficient oxygen change.…”
Section: Respirationmentioning
confidence: 99%